2023
DOI: 10.1037/ser0000557
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs of homeless U.S. veterans by gender and race/ethnicity: Data from five annual surveys.

Abstract: There has been insufficient research on gender, race, and ethnic differences in unmet needs of homeless populations. This study analyzed 5 years of data collected by Project Community Homelessness Assessment, Local Education, and Networking Groups (CHALENG) surveys from 2012 to 2016 to examine gender, race, and ethnic differences in "literally homeless" veterans (i.e., veterans living in the streets, shelters, vehicles, or any other place not meant for habitation). Of 7,040 participants, there were 6,335 male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…For example, Hispanic female Veterans experiencing homelessness were more likely to report needs around domestic violence (aOR = 2.26, 95% CI: 1.02–5.02), food and transportation (aOR = 3.96, 95% CI: 1.82–8.63), and Black female Veterans had higher substance use treatment needs (aOR = 2.85, 95% CI: 1.23–6.64) compared to other racial categories. 53 Stigma was also noted to be a barrier to accessing healthcare and social services. Female Veterans discussed the stigma attached to PTSD and MST in the military 25 and the stigma around housing insecurity 54 prevented them from disclosing their need for additional services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hispanic female Veterans experiencing homelessness were more likely to report needs around domestic violence (aOR = 2.26, 95% CI: 1.02–5.02), food and transportation (aOR = 3.96, 95% CI: 1.82–8.63), and Black female Veterans had higher substance use treatment needs (aOR = 2.85, 95% CI: 1.23–6.64) compared to other racial categories. 53 Stigma was also noted to be a barrier to accessing healthcare and social services. Female Veterans discussed the stigma attached to PTSD and MST in the military 25 and the stigma around housing insecurity 54 prevented them from disclosing their need for additional services.…”
Section: Resultsmentioning
confidence: 99%
“…44 Female Veterans experiencing homelessness also reported increased unmet needs, particularly around emergency shelter (aOR = 1.4, 95% CI: 1.16-1.69) transitional housing (aOR = 1.51, 95% CI: 1.22-1.88)), and dental care (aOR = 1.42, 95% CI: 1.17-1.71). 53 When examining specific VA housing programs, although women were more likely to be admitted to HUD-VASH housing, they were less likely to be in Grant Per Diem (GPD) transitional housing (32.9% versus 41.5%, χ 2 = 116.8, p < 0.001) suggesting that there may be less available transitional housing for female Veterans to live in while they await the more permanent HUD-VASH housing. 10 This finding was supported by another study, which found female Veterans experiencing homelessness were less likely to be part of a group of VA homeless program users whose pattern of VA homeless program use over time was comprised heavily of transitional housing programs (7% in transitional programs versus 13%-18% in other programs).…”
Section: Comparison Of Male and Female Veterans' Access Or Use Of Hea...mentioning
confidence: 99%